2014
DOI: 10.14233/ajchem.2014.16786
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silica Fume as Low-Cost Absorbent Material for Nickel Removal from Aqueous Solutions

Abstract: The presence of heavy metals in the aquatic ecosystem causes harmful effects to living organisms and causes environmental hazards 1. Inorganic effluents contaminate wastewater with toxic metals such as Ni, Cr, Cd, Hg, Pb and Zn 2-4. These heavy metals are extremely toxic, non-biodegradable and accumulate in the food chain, even in relatively minute quantities. Thus, industries such as electroplating, aerospace and metal finishing are among the most hazardous from a wastewater viewpoint 5-6. For the past severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, due to the intrinsic parameters of the Langmuir isotherm model, plots gave a negative value of Langmuir constant, b, and the calculated maximum adsorption capacity, Q m, for Ni, as listed in Table 2. The results demonstrate that the Langmuir isotherm model was unsuitable to describe the adsorption process, as the adsorption behavior on the tested system was not following the assumption of the Langmuir isotherm approach [77]. In this context, the Freundlich model was suggested and more fitted to describe the isotherm of the Ni(II) adsorption on SA-β-CD/CNTs hydrogel.…”
Section: Effect Of Contact Time and Kinetic Studiesmentioning
confidence: 96%
“…However, due to the intrinsic parameters of the Langmuir isotherm model, plots gave a negative value of Langmuir constant, b, and the calculated maximum adsorption capacity, Q m, for Ni, as listed in Table 2. The results demonstrate that the Langmuir isotherm model was unsuitable to describe the adsorption process, as the adsorption behavior on the tested system was not following the assumption of the Langmuir isotherm approach [77]. In this context, the Freundlich model was suggested and more fitted to describe the isotherm of the Ni(II) adsorption on SA-β-CD/CNTs hydrogel.…”
Section: Effect Of Contact Time and Kinetic Studiesmentioning
confidence: 96%
“…Wang et al (2011) found that the performance of silica fume in adsorption of Rhodamine B from aqueous solutions is better than from coal ash (Wang & Chu, 2011). Kalkan et al (2014) found silica fume has a high capacity to adsorb nickel (Kalkan, Nadaroglu, & Celebi, 2014). Nadaroglu et al (2013) and Ahmed et al (2015) showed that silica fume is a cheap and effective adsorbent for the removal of cadmium (II) and copper and zinc ions from wastewater (Ahmed et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Baraka et al studied heavy metal removal of melamine‐formaldehyde‐dietheylenetriaminepentaacetic acid, and found its absorption mechanism was attributed to the chelate between amino and divalent toxic metal ions 10 . Furthermore, clay, 11 and silicates are the low‐cost adsorbent, 12‐14 including micritic limestone, 15 zeolite, 16 bentonite. Therein, bentonite is a clay type consisting of montmorillonite primarily, comparatively cheaper and commonly used adsorbent because of its unique high surface area and high ion exchange rate, thereby gaining increasing attention in wastewater treatment in recent years 17,18 .…”
Section: Introductionmentioning
confidence: 99%